Differences in the Quality of Movement Functionality between Judokas, Karatekas, and Non-Athletes - Amel Mekic; Erol Vrevic; Pavle Malovic; Safet Kapo; Husnija Kajmovic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2020)
Judo and karate are polystructural acyclic sports, which require development of a great number of human abilities and characteristics. Although both are martial arts, they differ greatly in the requirements and quality of performance of individual movements. The aim of this study was to determine the differences in the quality of performing movements between karatekas, judokas and non-athletes. The respondents were 60 young people (14.1 - 14.6 years), 20 of which belonged to the group of "judokas", 20 to the group of "karatekas" and 20 to the group of "non-athletes". All individuals were physically and mentally healthy, and were fit to undergo testing. The sample of variables consisted of 7 tests, which belong to the Functional Movement Screen (FMS) method of testing the movement functionality. By using the ANOVA test, in 4 variables showed up statistically significant difference (p<0.05). Group of non-athletes has the lowest values in all tests, especially in deep squat, active straight-leg raise, and rotary stability. Judokas performed the lowest values in the shoulder mobility test. The main conclusions of this paper are that training content should be specific to sports, and sports (in this case martial arts) have a positive effect on the development of the locomotor system, which could be useful for properly perform basic movements which humans use in everyday life.